Variations of Anterior Skull Base Seen on Computed Tomography Scans of the Paranasal Sinuses - Salonee Shenoy; Prashant H. Patil; Nitin R. Ankle; Ajinkya V. Jadhav (Journal of the Scientific Society)
Context: The anterior skull base (ASB) and the paranasal sinuses are known for anatomical variations. Therefore, a preoperative assessment for the assessment of these variations is a necessity. This study aims to determine the profile of variations of the ASB using computed tomography of the paranasal sinuses (CT-PNS) scans. Settings and Design: Observational Study. Materials and Methods: Forty CT-PNS scans were studied with measurement of different parameters. Statistical Analysis: Observational study analysis – Descriptive stats, t-tests, Chi-square, nonparametric tests, analysis of variance, regression, P < 0.05 significance level. A significance level of P < 0.05 was used for all tests. Results: Seventeen male and 23 female CT-PNS scans were studied. Different measurements on the right and left sides, as well as between genders, were examined and compared. The supraorbital ethmoidal cell is the most often seen anatomical variation. Variations in the ASB are equally visible on both sides in men and on the right in females (Type-II > Type-1). Type I was more common among female, whereas Type II was more common. The existence of the anterior ethmoidal foramen is a dependable marker for the anterior ethmoidal artery. In the group under investigation, there was no lamina papyracea abnormality. Conclusion: This study aims to assess anatomical variations in the Indian population undergoing ASB surgeries, contributing to the current understanding of Indian paranasal sinuses and skull base dynamics.